URBAN STUDENTS SELF-EFFICACY PROFILE ON MATHEMATICS LEARNING: INSTRUMENT VALIDATION AND EVALUATION - Masrianti Fadillah; Tengku Abdani Murazanty; Ranny Mukerdi; Rahmadini Fitri; Fitri Nur Ashari; Indra Saputra; Annisah Zaeri; Akbar Septiawan (Mathematics Research and Education Journal, 2024)
This research aims to determine students' self-efficacy regarding mathematics learning outcomes. The type of research used in this research is descriptive research. The population in this study were junior high school students in Pekanbaru City, with the sample consisting of 49 students from SMP Negeri 25 Pekanbaru and SMP Negeri 34 Pekanbaru consisting of 53 students. The sampling technique in this research was simple random sampling. The data collection technique in this research was carried out by survey using questionnaires and interviews. Data analysis in this study used descriptive statistics. The results obtained from the analysis of students' self-efficacy regarding mathematics learning outcomes are in the not good category with a percentage of 55%, and 45% are in the good category. The evaluation results show that the self-efficacy of students at SMP Negeri 25 Pekanbaru and SMP Negeri 34 Pekanbaru regarding mathematics learning outcomes is in the not-good category. Teachers should play a more active role as companions, mentors, directors, and motivators in mathematics learning. With this, students will feel confident in their ability to solve mathematical problems in learning materials that are considered difficult, which will further increase students' self-efficacy regarding mathematics learning outcomes.